Boekbesprekingen - Kwakkel, Gert (Theologia reformata, 2024)
Bijbelwetenschappen: Joachim J. Krause/Kristin Weingart (red.) - Exegetik des Alten Testaments: Bausteine für eineTheorie der Exegese; Charlie Trimm - The Destruction of the Canaanites: God, Genocide, and Biblical Interpretation; Willem J. Ouweneel - De Sjechinah, de Torah, de Messias vanuit joods en christelijk zicht; Matthew V. Novenson/R. Barry Matlock (red.) - The Oxford Handbook of Pauline Studies. Kerk- en theologiegeschiedenis: F. Ledegang - In dialoog met de natuur. Vroegchristelijke denkers over het scheppingsverhaal; Regina D. Schiewer/Stefan Seber (red.) - Hans-Jochen Schiewer, Schriften zur geistlichen Literatur und zur Frömmigkeitskultur des Mittelalters; Anne Bezzel - Leibhaftige Frömmigkeit. Die Verehrung der Seitenwunde Christi als Schnittfläche und Fluchtpunkt spätmittelalterlicher Frömmigkeitsphänomene; Christian Link - Die Theologie Calvins im Rahmen der europäischen Reformation; Peter Lake - On Laudianism: Piety, Polemic and Politics During the Personal Rule of Charles I; Henk van den Belt/Klaas-Willem de Jong/Wim van Vlastuin (red.) - A Landmark in Turbulent Times. The Meaning and Relevance of the Synod of Dordt (1618-1619); Cory C. Brock/N. Gray Sutanto - Neo-Calvinism. A Theological Introduction; Johan Snel - Abraham Kuyper, een leven in de journalistiek. Een alternatieve biografie; Lukas Bormann/Michael Heymel (red.) - Martin Niemöller - Brüche und Neuanfänge: Beiträge zu seiner Biographie und internationalen Rezeption; Jelle Horjus - Wij moeten wat meer durven: biografie Jannes Reiling (1923-2005); Catherine E. Clifford/Massimo Faggioli (red.) - The Oxford Handbook of Vatican II. Systematische theologie: Brandon D. Crowe - Why Did Jesus Live a Perfect Life? The Necessity of Christ’s Obedience for Our Salvation; Paul Dafydd Jones - Patience - A Theological Exploration: Deel 1, From Creation to Christ; Paul Tyson - A Christian Theology of Science. Reimagining a Theological Vision of Natural Knowledge. Cultuur: Jan van Helden - Reformed Modernity. Discerning the work of the Sprit in humanist solidarity culture in Western Europe from a Reformed perspective.